On the use of CFD to obtain head loss coefficients in hydraulic systems and its application to liquid metal MHD flows in nuclear fusion reactor blankets. (22nd October 2021) - Suarez, Daniel; Mas de les Valls, Elisabet; Batet, Lluis
Abstract: When an incompressible fluid flows through a contraction in a conduit, the increase in the kinetic energy of the fluid is accompanied by a pressure drop. This pressure drop is not to be assimilated with head loss. If downstream the fluid encounters an expansion in the conduit, the energy conversion will take place in the opposite way. Therefore, when a geometrical singularity is analysed to assess its contribution to the pumping power requirements of the system, the whole mechanical energy transfer of the fluid in the singularity has to be taken into account, and not only the pressure variation. The first part of the present work establishes a method to obtain head loss coefficients in geometric singularities of hydrodynamic circuits using the results of computational fluid dynamics (CFD) calculations. These coefficients are of interest when modelling the whole system with a 1D system code, for instance. In the second part of the article, the method is applied to a more complex case, involving magnetohydrodynamic (MHD) phenomena. Thus, a prototypical channel singularity in a liquid metal circuit subject to a magnetic field is analysed. The layout is representative of a case that could be found in the liquid metal blankets to be used in nuclear fusion reactors. The influence of the MHD phenomena is studied and the differences with a purely hydrodynamic case are pointed out. The MHD analyses have been done in the Marconi High Performance Computing facility, using 48 cores, each case needing between one and two weeks to complete.